World oil prices and agricultural commodity prices: The evidence from China - Zhengwei MA; Rui XU; Xiucheng DONG (Agricultural Economics (AGRICECON), 2015)
It is acknowledged that crude oil prices affect agricultural prices through both direct and indirect transmission schemes (i.e. exchange rate). In China, the matter of energy security may be immediately transmitted to the food security, imposing a pressure to China's macro-economy to a certain extent. This paper examines the long-run and short-run influence caused by the world crude oil prices and the RMB-dollar exchange rate on the five individual agricultural commodity prices (soybean, maize, wheat, colza oil, and japonica rice) in China. In this paper, the Granger causality approach is applied to test the long-run interrelationships with the weekly data from June 2002 to August 2013. In addition, the impulse-response analysis is utilized to study how the agricultural prices react to the sudden shocks in oil prices and exchange rate in the short term. The results reveal that the impulse response curves demonstrate that agricultural prices are not significantly affected by the abrupt changes in either oil prices or the exchange rate. Consistently, agricultural prices are neutral to the changes in oil prices in the long run while the exchange rate only Granger causes the prices of soybean. Ultimately, we present some sound reasons to explain the statistical results and propose some policy suggestions aimed at the China's food and energy security.